THE RELEVANCE AND APPLICATION OF QISAS IN CONTEMPORARY CONTEXTS: A QUR’AN PERSPECTIVE - Suarning, Suarning; Haq, Islamul; Fikri, Fikri; Aminah, St.; Resi, Resi; Ar, Zulfahmi (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
The concept of qisas punishment in the Holy Qur’an remains a focal point of scholarly debate in the modern era, particularly regarding its implementation within contemporary Islamic legal systems and its compatibility with international human rights standards. This study examines the enduring relevance of qisas in modern Sharia and investigates how its application can be harmonized with the principles of social justice, equality, and universal human values. Utilizing a qualitative approach and a case study method, this research explores classical Islamic legal sources, historical contexts, contemporary scholarly interpretations, and comparative practices of qisas enforcement across Muslim-majority countries. The findings reveal considerable diversity in the interpretation and implementation of qisas. While some countries maintain a retributive framework emphasizing proportional justice and legal uniformity, others adopt restorative models that prioritize reconciliation, forgiveness, and communal harmony. The study argues that qisas retains its relevance when understood within an adaptive and dynamic Islamic legal framework responsive to contemporary legal developments and evolving ethical norms. By situating qisas within broader discourses of restorative justice and human dignity, this research contributes to ongoing discussions on Islamic legal reform and underscores the potential of qisas to function as a humane, progressive, and socially responsive component of justice systems in the modern world.